2023
DOI: 10.1097/shk.0000000000002102
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen alleviates post-hemorrhagic shock mesenteric lymph-mediated lung injury through autophagy inhibition

Abstract: Background: Hemorrhagic shock–induced acute lung injury (ALI) is commonly associated with the posthemorrhagic shock mesenteric lymph (PHSML) return. Whether excessive autophagy is involved in PHSML-mediated ALI remains unclear. The relationship between estrogen treatment and PHSML or autophagy needs to verify. The current study will clarify the role of estrogen in reducing PHSML-mediated ALI through inhibition of autophagy. Methods: First, a hemorrhagic shock model in conscious rats was used to observe the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Imaging was performed using an ImageQuant LAS 4000 apparatus (GE Co., Boston, MA). The protein expression level was normalized to the internal reference β-actin using Quantity One software (version 4.6.2; Bio-Rad Co., Hercules, CA) (20).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Imaging was performed using an ImageQuant LAS 4000 apparatus (GE Co., Boston, MA). The protein expression level was normalized to the internal reference β-actin using Quantity One software (version 4.6.2; Bio-Rad Co., Hercules, CA) (20).…”
Section: Methodsmentioning
confidence: 99%
“…Under inhalation anesthesia with 2% isoflurane (Shenzhen Ruiwald Life Technology Co., Ltd., Shenzhen, China) by the inhalation anesthesia machine for small animals (MATRX VMR; Midmark Corporation, Dayton, OH), before the surgical and hemorrhage procedures, either the authentic or sham SGB procedures were performed according to previous reports, with minor alterations (12,(15)(16)(17). After hemorrhagic shock (40 mm Hg for 90 min, followed by resuscitation with shed whole blood and equal Ringer's solution), the PHSML and PHSML-SGB were harvested from rats under anesthetic conditions (18)(19)(20).…”
Section: Experimental Design and Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Studies have shown that inhibiting LPS-induced excessive autophagy in alveolar epithelial cells can mitigate inflammatory injury. 25,26 Moreover, excessive autophagy activation has been implicated in the development of ALI, [27][28][29][30] and the effective inhibition of autophagy is a potential therapeutic approach. Thus, modulating autophagy from inducing death to supporting survival could prove effective in the treatment of LPS-induced ALI.…”
Section: Introductionmentioning
confidence: 99%
“…Acute lung injury (ALI) is a life-threatening pathological respiratory process caused by infection, trauma, radiation, ischemia reperfusion (IR), and other factors (1)(2)(3). Acute lung injury is characterized by increased permeability of the alveolar-capillary membrane, edema, low pulmonary compliance, high pulmonary dead space, diffuse alveolar injury, and even acute hypoxic respiratory failure (4)(5)(6). The basic pathological changes in ALI are injury to alveolar epithelial cells, pulmonary microvascular endothelial cells (7), and alveolar macrophages (8), and its severe clinical manifestation is acute respiratory distress syndrome (ARDS) (9).…”
Section: Introductionmentioning
confidence: 99%